“Modern and Contemporary Art: Topical Abstraction in Contemporary Sculpture” Special Issue Introduction - Elyse Speaks; Susan Richmond (Arts, 2024)
The essays gathered in this Special Issue of Arts concern artists working in the United States and Europe since the 1960s who have leveraged sculptural abstraction to address topical issues without ceding to the classical framework of figuration [...]